Эволюция понятия фонемы в современной лингвистике - Шестакова, Е.Г. (Культура народов Причерноморья, 2002)
The notion of phoneme, which had been introduced in the end of 19th century, was considered during the last
century by representatives of different linguistic schools from various sights. There arose several interpretations of the
concept “phoneme”. To receive a complete notion of this unit of the sound system of the language one ought to take into
consideration conceptions of all of these linguists, who used to work at this problem.